Principles of Using New Educational Technologies in Teaching Geography to School Students - N. S. Urinova (Global Scientific Publishing, 2022)
"Geography" science has a unique role in expanding the effectiveness of the educational process in general secondary schools. For this, the use of non-traditional teaching methods in the teaching of "Geography" is of great importance. The article describes recommendations about the possibilities of using non-traditional teaching methods in the teaching of "Geography".
Keywords: Non-traditional lesson; geography education; base signals